Quality of care for citizens of the Registry Office of the National Registry of Identification and Civil Status, Lima - Charry Aysanoa, Juan Marciano (2021)
Objective: the present research aims to explain the perception of citizens regarding the quality of care in the Registry Office of the National Registry of Identification and Civil Status (RENIEC). Materials and methods: it assumes the positivist paradigm and quantitative approach, basic type, descriptive level and non-experimental, cross-sectional design. The study setting was the RENIEC office, province and department of Lima. The population consisted of 1500 citizens who carry out procedures in a single day; the sample was chosen probabilistically and represented 305 citizens in three specific areas: Reports, Procedures and Civil Registry. The technique used was the survey and the valid and reliable instrument was applied: SERVQUAL, which assesses the perceptions and expectations regarding the services users receive. Results and conclusions: citizens who carry out procedures before the RENIEC qualify as medium the quality of the service provided by the citizenship and civil status registry institution. Citizen expectations and perception show negative values, which means that users do not show confidence that care will improve, at least in a short time. As for the environment where they work, it is not in accordance with social needs to develop good quality.